CODEX weak lensing mass catalogue and implications on the mass–richness relation. Issue 1 (23rd December 2020) - Kiiveri, K; Gruen, D; Finoguenov, A; Erben, T; van Waerbeke, L; Rykoff, E; Miller, L; Hagstotz, S; Dupke, R; Patrick Henry, J; Kneib, J-P; Gozaliasl, G; et al.
ABSTRACT: The COnstrain Dark Energy with X-ray clusters (CODEX) sample contains the largest flux limited sample of X-ray clusters at 0.35 < z < 0.65. It was selected from ROSAT data in the 10 000 square degrees of overlap with BOSS, mapping a total number of 2770 high- z galaxy clusters. We present here the full results of the CFHT CODEX programme on cluster mass measurement, including a reanalysis of CFHTLS Wide data, with 25 individual lensing-constrained cluster masses. We employ lensfit shape measurement and perform a conservative colour–space selection and weighting of background galaxies. Using the combination of shape noise and an analytic covariance for intrinsic variations of cluster profiles at fixed mass due to large-scale structure, miscentring, and variations in concentration and ellipticity, we determine the likelihood of the observed shear signal as a function of true mass for each cluster. We combine 25 individual cluster mass likelihoods in a Bayesian hierarchical scheme with the inclusion of optical and X-ray selection functions to derive constraints on the slope α, normalization β, and scatter σln λ|μ of our richness–mass scaling relation model in log-space: ${\langle {\rm In}\, \, λ\!\!\mid\!\!μ\rangle = αμ + β, } $ with μ = ln ( M 200 c / M piv ), and M piv = 10 14.81 M⊙ . We find a slope $α = 0.49^{+0.20}_{-0.15}$, normalization $\exp (β) = 84.0^{+9.2}_{-14.8}$, and $σ _{\ln λ | μ } = 0.17^{+0.13}_{-0.09}$ using CFHT richness estimates. In comparison to other weak lensing richness–mass relations, we find the normalization of the richness statistically agreeing with the normalization of other scaling relations from a broad redshift range (0.0 < z < 0.65) and with different cluster selection (X-ray, Sunyaev–Zeldovich, and optical).